Síntese, Caracterização Estrutural e Análise do Potencial Catalítico, para a Preparação de Biodiesel, de Niobatos Não Estequiométricos com Estrutura Tungstênio Bronze - Zangirolamo, Eliára Quirino [UNESP] (2014)
Niobates with tetragonal tungsten bronze TTB-type structure have been studied for their electrical properties and optical applications. In the catalysis field, niobium compounds are reported as catalysts or supports in various processes such as oxidative dehydrogenation of alkanes oxidative coupling of methane and dry reforming of methane. In this sense, the present work describes the preparation and characterization of a catalyst carried out from niobium with TTB structure, for preparation of biodiesel via ethyl route. From NaSr2Nb5O15 system was investigated the non stoichiometric niobates with chemical formula NaSr2Nb4,75O15-δ and NaSr2Nb4,5O15-δ. All systems were prepared by chemical synthesis using the Modified Polyol method. The thermal decomposition of the precursor powders of NaSr2Nb5O15 and their solid solutions were investigated by thermogravimetric analysis (TG) and differential scanning calorimetry (DSC). The DSC curve showed an endothermic event at around 860°C, related to the early formation of the crystalline phase of NaSr2Nb5O15. The structural characterization of powders was performed by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. The structural parameters were determined by refinement using the Rietveld method, considering the space group P4bm, and the best theoretical adjustment was obtained by assuming that each octahedral site was occupied by Nb5+ ions, each pentagonal site was statistically occupied by an equal amounts of Na+ and Sr2+ ions and tetragonal site by Sr2+ ions. The products of the catalytic reaction for biodiesel production were analyzed by Fourier transform infrared spectroscopy and gas chromatography coupled mass. The greater catalytic efficiency was observed for the NaSr2Nb4,5O15-δ and identified by the presence of ethyl esters peaks in the chromatogram